2004
DOI: 10.1016/j.jtcvs.2003.08.032
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of coronary bypass surgery with and without cardiopulmonary bypass in patients with multivessel disease

Abstract: In 4 centers with beating-heart operation experience, there is an overall early benefit in off-pump surgery, especially in patients traditionally considered at high risk for coronary artery bypass grafting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
115
4
9

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(135 citation statements)
references
References 16 publications
4
115
4
9
Order By: Relevance
“…On-pump CABG activates the complement and fibrinolytic cascade, contributing to postoperative bleeding [12]. In our study, we observed lower rates of hemorrhagic shock and also decrease in the need for blood transfusions in the OPCAB group compared to on-pump CABG group.…”
Section: Discussionsupporting
confidence: 58%
“…On-pump CABG activates the complement and fibrinolytic cascade, contributing to postoperative bleeding [12]. In our study, we observed lower rates of hemorrhagic shock and also decrease in the need for blood transfusions in the OPCAB group compared to on-pump CABG group.…”
Section: Discussionsupporting
confidence: 58%
“…In one initial phase of the experiment, the occurrence of arrhythmia and hemodynamic instability is expected even during the preparation of anastomoses in the anterior wall, which, with experience, rarely happens even when three or four grafts into the lateral and posterior heart walls are necessary. Studies suggest a great benefit of off-pump surgeries compared to conventional surgeries [24][25][26], which are already giving good results over the medium term [27][28][29]. With the greater advances in interventionist cardiology, the heart surgeon is put under great pressure to use less invasive surgery and provide excellent results, which, we believe, start with offpump surgeries.…”
Section: Resultsmentioning
confidence: 99%
“…Bottio et al [29] in a prospective study with 324 patients who underwent CABG, of whom 216 underwent on-pump CABG and 108 underwent off-pump, observed there was a lower incidence of sternal dehiscence with mediastinitis in the off-pump group, although this difference was not statistically significant. Mack et al [30] observed a lower incidence of wound infection in patients undergoing off-pump compared to on-pump. Sabik et al [31] in the Cleveland Clinic study involving 812 patients undergoing CABG (half on-pump and half off-pump) have identified a higher incidence of wound infection in the onpump group (2.0% versus 0.2%, P = 0.04).…”
Section: Discussionmentioning
confidence: 97%